Decolonizing “Muslim Questions” in Europe: Integration and Entanglements of Colonial Epistemologies - Dinata, Septa; Sahrasad, Herdi (CIC Lembaga Riset dan Konsultan Sosial, 2025)
Europe’s so-called “Muslim question” is less an inevitable cultural clash than the prolonged imprint of colonial hierarchies, secular assimilation, and racialized security politics. This dynamic has roots in post–World War II labor migrations. These movements, far from simple economic exchanges, transplanted colonial hierarchies into Europe’s social fabric. From the Rushdie Affair to the post-9/11 security turn, public debates, and state policies, however, have repeatedly reframe Muslim presence as a challenge to national cohesion and public order. Addressing this requires a decolonial rethinking of integration, one that dismantles colonial epistemologies and recognizes Muslims as co-authors of Europe’s plural identity. Edward Said’s critique of orientalism, analysis of secular power introduced by Talal Asad, vision of counter-hegemonic Islamism proposed by Salman Sayyid, and Dipesh Chakrabarty’s call to “provincialize” Europe together reveal how colonial logics continue to shape Muslim integration. Foregrounding Muslim agency through Ramadan’s reformist “European Islam” and Fanon’s radical pedagogy, and guided by the insurgent energies of decolonial praxis, this study calls for a decisive rupture from assimilationist orthodoxies toward cultural equity and ethical pluralism. It thus advances a future that will help to weave a participatory polis that transcends postcolonial melancholia and affirms diversity as a civic strength.